On the compressive behavior of an FDM Steward Platform part. Issue 4 (12th June 2017) - Vidakis, Nectarios; Petousis, Markos; Vairis, Achilles; Savvakis, Konstantinos; Maniadi, Athena
Graphical abstract: Abstract: Acrylonitrile–butadiene–styrene (ABS) is commonly used material in the fused deposition modeling (FDM) process. In this work, ABS and ABS plus parts were built with different building parameters and they were tested according to the ASTM D695 standard. Compression strength results were compared to stock ABS material values. The fracture surfaces of selected specimens were examined under a Scanning Electron Microscope (SEM), to determine the failure mode of the filament strands. Following this a Steward Platform part was tested under compression in a tensile testing machine. The experimental results were employed to develop a finite element model of the Steward Platform part, in order to determine the maximum force the part can withstand. The Finite Element Model results were in good agreement with the values measured in the Steward Platform part compressive tests, demonstrating that the model developed is reliable. In these experiments, it was found that ABS parts build with a larger layer thickness showed lower compressive strength, which ABS plus did not show. ABS specimens on average developed about half the compressive strength of the ABS plus specimens, while the ABS plus specimens showed lower compressive strength values than stock ABS material.